PENGARUH STRES KERJA DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KARYAWAN PADA PT PRATAMA ABADI INDUSTRI TANGERANG SELATAN - Nurhasanah, Siti; Priadi, Andri (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the effect of work stress and work discipline on employee productivity at PT Pratama Abadi Industri South Tangerang, partially and simultaneously. The research method used is a quantitative method. The sampling technique used the Slovin technique and the sample obtained in this study was 83 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of this research are Y = 37.903 + 0.275X1. The correlation coefficient value obtained is -0.412, meaning that the two variables have a moderate level of relationship. The determination value is 17%. Hypothesis testing obtained a calculated t value < t table or (-4.074 > 1.989). Thus, H0 is rejected and H1 is accepted, meaning that there is an influence of work stress on employee productivity. Y = 37.903 + 0.234X2. The correlation coefficient value obtained is 0.345, meaning that the two variables have a low level of relationship. The determination value is 11.9%. Hypothesis testing obtained a calculated t value > t table or (3.308 > 1.989). Thus, H0 is rejected and H1 is accepted, meaning that there is an influence of work discipline on work productivity. Y = 37.903 + 0.275X1 + 0.234X2. The correlation coefficient value obtained is 0.294, meaning it has a low relationship. The coefficient of determination value is 29.4%. Hypothesis testing obtained a calculated F value > F table or (16.687 > 3.11). Thus, H0 is rejected and H1 is accepted, meaning that there is a significant simultaneous influence of work stress and work discipline on employee productivity at PT Pratama Abadi Industri South Tangerang